Lactobacillus reuteri-derived γ-amino butyric acid alleviates MPTP-induced Parkinson’s disease through inhibiting ferroptosis via the AKT-GSK3β-GPX4 axis - Xuechao Dong; Teng Yang; Zheng Jin (npj Parkinson's Disease)
Abstract Parkinson’s disease (PD) is a debilitating neurological disorder characterized by motor dysfunction, which has been associated with alterations in the gut microbiota. Lactobacillus reuteri (L. reuteri), a safe and versatile probiotic, exhibits potent immunomodulatory functions and neuroprotective effects. However, the extent and mechanisms by which L. reuteri mitigates PD remain unclear. Here, we demonstrated that L. reuteri significantly alleviated MPTP-induced PD in mice. Importantly, we found that the protective effects of L. reuteri are mediated by its bioactive metabolites rather than the bacteria themselves. Specifically, L. reuteri elevated the levels of γ-aminobutyric acid (GABA). Administration of GABA to mice mitigated MPTP-induced PD. Mechanistically, GABA inhibited MPTP-induced ferroptosis in neuronal cells through activation of the AKT-GSK3β-GPX4 pathway via the GABA receptor. Collectively, our research elucidates that L. reuteri-derived GABA attenuates MPTP-induced PD by inhibiting ferroptosis via the AKT-GSK3β-GPX4 axis, providing a potential therapeutic approach for the prevention and treatment of PD.